Corporate governance, responsibility and sustainability : initiatives in emerging economies - Banik, Arindam (Palgrave Macmillan, 2015)
Corporate Governance, Responsibility and Sustainability investigates various dimensions of corporate governance issues in key emerging economies such as China, India, Brazil, South Africa and Russia. The book explores a number of issues in the areas of corporate governance framework, market discipline and building an efficient, competitive market.